Layer‐by‐Layer Assembled Heteroatom‐Doped Graphene Films with Ultrahigh Volumetric Capacitance and Rate Capability for Micro‐Supercapacitors. (29th April 2014) - Wu, Zhong‐Shuai; Parvez, Khaled; Winter, Andreas; Vieker, Henning; Liu, Xianjie; Han, Sheng; Turchanin, Andrey; Feng, Xinliang; Müllen, Klaus
<x xml:space="preserve">Abstract</x> Highly uniform, ultrathin, layer‐by‐layer heteroatom (N, B) co‐doped graphene films are fabricated for high‐performance on‐chip planar micro‐supercapacitors with an ultrahigh volumetric capacitance of ∼488 F cm−3 and excellent rate capability due to the synergistic effect of nitrogen and boron co‐doping. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>